The genus Ctenomelynthus (Hemiptera: Heteroptera: Coreidae: Acanthocephalini), with the description of three new species and key to the known species - Brailovsky, Harry (Zootaxa, 2018)
The genus Ctenomelynthus Breddin (1903) is redescribed, and three new species: C. sanchezi from French Guiana, and Venezuela, C. urbinus from Brazil, and C. venustulus from Suriname are described. Ctenomelynthus willineri (Kormilev, 1952), is synonymized under C. coxalis Breddin, 1903. One species, C. bridarollii (Kormilev) is designated as a nomen dubium. New distributional records for C. brunneiventris Breddin, C. coxalis Breddin, and C. inermibus (Distant) are included. Dorsal and ventral photographs and parameres of some species are included. A key to the six known species is given.